Impact of encryption and decryption techniques for high speed optical domain - Singh, Rishabh; Kumar, Ghanendra; Kumar, Chakresh (Computer Science and Information Technologies, 2021)
This project proposes the design of ultrafast communication circuit which can enable the high speed secured data transmission at 50 Gb/s and 100 Gb/s by the use of distributed Raman amplifier, erbium – doped fiber amplifier (EDFA), filter, single mode fiber along with fiber bragg grating (FBG) and attenuators. The simulation of the suggested optical circuit involves the use of parameters of Raman amplifier and EDFA and other components included in the optical structure. The design also includes the use of encryption and decryption techniques to ensure secured communication. Thus, realization of these circuits at 50 Gb/s and 100 Gb/s will enable the future optical communication applications for ultrafast data transmission to large distances.